2015
DOI: 10.3892/etm.2015.2418
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of post-infectious bronchiolitis obliterans in children undergoing long-term azithromycin treatment

Abstract: Abstract. The aim of the present study was to outline any predisposing factors and clinical and radiological features of post-infectious bronchiolitis obliterans (PIBO) in pediatric patients, and to determine the effect of long-term azithromycin treatment on these factors. In total, 16 cases of children with PIBO were retrospectively reviewed. Adenovirus and Mycoplasma pneumoniae were the most common etiological agents (12/16) in the children with PIBO. The patients presented with persistent dyspnea, a chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 29 publications
5
23
1
6
Order By: Relevance
“…It is known that 14% to 60% of children with documented adenovirus LRTIs have some degree of pulmonary sequelae 9 . Wang et al 8 found that adenovirus and M. pneumoniae were the most common etiologic agents of PIBO. Similarly, we found that adenovirus was the most common infectious agent giving rise to PIBO; there was one patient with adenovirus infection in group 1 and five patients in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that 14% to 60% of children with documented adenovirus LRTIs have some degree of pulmonary sequelae 9 . Wang et al 8 found that adenovirus and M. pneumoniae were the most common etiologic agents of PIBO. Similarly, we found that adenovirus was the most common infectious agent giving rise to PIBO; there was one patient with adenovirus infection in group 1 and five patients in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…The children with PIBO are frequently hospitalized with acute exacerbation due to respiratory infection and so were the patients enrolled in this study. However, clinical differentiation of PIBO exacerbation from acute bronchiolitis in young children is often challenging, which might cause treatment delay [7]. The search for non-invasive biomarkers for early diagnosis is needed to prevent chronic lung function impairment associated with PIBO.…”
Section: Discussionmentioning
confidence: 99%
“…They also need frequent hospitalization because of acute exacerbation due to respiratory infection during the first disease years. Clinical differentiation of PIBO exacerbation from acute bronchiolitis in young children is often challenging, which may result in treatment delay and chronic lung function impairment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bronşiyolitis obliterans, terminal ve respiratuvar bronşiyollerin kronik inflamasyonu, lümen içi granülasyon dokusu oluşumu, peribronşiyal fibrozisi ve tüm bunların sonucun-da meydana gelen distal hava yollarının kısmî ya da tam obstrüksiyonu ile karakterize, morbidite ve mortalitesi yüksek, kronik bir akciğer hastalığıdır 5,6,9 . İnhale edilen toksik gazlar, immünolojik hastalıklar, aspirasyon sendromları, organ nakilleri (akciğer ve kemik iliği), kollajen doku hastalıkları, Steven-Johnson sendromu ve solunum yolu enfeksiyonları (postenfeksiyöz) hastalıktan sorumlu sebepler arasında gösterilmektedir 6 .…”
Section: Discussionunclassified
“…İnhale edilen toksik gazlar, immünolojik hastalıklar, aspirasyon sendromları, organ nakilleri (akciğer ve kemik iliği), kollajen doku hastalıkları, Steven-Johnson sendromu ve solunum yolu enfeksiyonları (postenfeksiyöz) hastalıktan sorumlu sebepler arasında gösterilmektedir 6 . Çocuk yaş grubunda sıklığı tam olarak bilinmeyen bu hastalık, çoğunlukla virusların sebep olduğu solunum yolu enfeksiyonlarına ikincil olarak ortaya çıkmaktadır 5,6,9 . En sık tespit edilen viral etken adenovirus olup, bunu RSV, parainfluenza, influenza, su çiçeği ve kızamık izlemektedir.…”
Section: Discussionunclassified